Spermatogenesis and semen quality of male muntjak (Muntiacus muntjak muntjak) during antler growth periods - Sri Wahyuni; Srihadi Agungpriyono; Muhammad Agil; Idawati Nasution; . Hamny; Tuty L. Yusuf (Syiah Kuala University, 2012)
Muntjak (Muntiacus muntjak muntjak) belongs to Cervidae family which distributed in Java Island and Southern part of Sumatera. This cervid has been protected by Indonesian Government since 1999. In order to support breeding program of the species and to avoid them from extinction, itsreproductive biology such as spermatogenesis and the correlation to semen quality is important to be investigated. Therefore, the objective of this study was to examine spermatogenesis and semen quality of two adult male muntjaks during antler growth periods that consist of hard antler (H), casting (C), andvelvet antler (V). Testicular tissues and semen (ejaculates) were obtained by core needle biopsy and electroejaculation methods respectively. Testicular tissues were processed histologically and stained with periodic acid Schiff (PAS) to observe spermatogenesis whereas semen was evaluated to obtaine itsquality. The results showed that spermatogenic activities were detected in all antler periods which marked by PAS positive staining (magenta colour) of round and elongated spermatid acrosomes. In H period, spermatogenic activity was higher than those C and V periods. According to semen evaluation,motile spermatozoa were found with different concentration in all antler periods. The highest sperm concentration (x 106 spermatozoa/ml) in both of muntjaks was found in H period (506.25 ± 61.87), and slightly decreased in C (288.75 ± 37.12), and V periods (362.60 ± 17.68). These finding showed thatspermatogenesis to produce spermatozoa is taken place while muntjaks are in C and V periods with differ activities that provable with the existence of motile spermatozoa from ejaculates in both of male muntjaks. Therefore, muntjaks could provide reproductive function throughout the year of reproductiveaseasonality which is similar to the reeves and formosan muntjaks